Predictors Affecting Millennial Generation Work Satisfaction in Pematangsiantar City: a Quantitative Approach - Ady Inrawan; Ruth Tridianty Sianipar; Hery Pandapotan Silitonga; Acai Sudirman; Edy Dharma (Applied Quantitative Analysis, 2021)
In running the company's operations, skilled and expert human resources are needed to run it to achieve its goals effectively and efficiently. Supporting the role of skilled and expert human resources, optimal job satisfaction is needed for employees to encourage increased performance. The aim of this study is to determine the predictors that affect the job satisfaction of millennial workers in Pematangsiantar City. This research instrument used a questionnaire distributed to 120 respondents who worked in companies and banks. Next, the researcher tested the hypothesis using Structural Equation Modeling (SEM) based on a variant called Partial Least Square (PLS) and the SmartPLS version 3.0 application as a tool to analyze it. The results of this study concluded that five hypotheses were accepted, and 1 hypothesis was rejected. The rejected hypothesis is that organizational justice has no significant effect on work satisfaction. Furthermore, significant results were obtained for the effect of organizational climate, organizational commitment, reward, and work environment on work satisfaction. Then, for the effect of work satisfaction on employee performance, significant results were obtained. For further research, the author recommends researchers develop variables that are suspected to be the main predictors to encourage job satisfaction and employee performance to provide complete recommendations regarding the development of human resource performance, especially for millennial workers. The novelty of this research is in measuring the level of satisfaction of millennial workers, considering that in 2030-2040 the Indonesia will get a substantial demographic bonus. The proposed model includes elements of organizational climate, organizational commitment, reward, organizational justice, and work environment to determine how much influence it has on the level of satisfaction and its impact on performance.